Sporothrix brasiliensis induces a more severe disease associated with sustained Th17 and regulatory T cells responses than Sporothrix schenckii sensu stricto in mice - Batista-Duharte, Alexander [UNESP]; Téllez-Martínez, Damiana [UNESP]; Roberto de Andrade, Cleverton [UNESP]; Portuondo, Deivys Leandro [UNESP]; Jellmayer, Juliana Aparecida [UNESP]; Polesi, Marisa Campos [UNESP]; Carlos, Iracilda Zeppone [UNESP] (Elsevier, 2018)
Little is known about the differences in the CD4+ T-cell response induced by Sporothrix schenckii and Sporothrix brasiliensis, the most virulent species that cause sporotrichosis. Here, the helper (Th) and regulatory T cells (Tregs) responses were evaluated comparatively in a murine model of sporotrichosis on days 7, 21 and 35 after subcutaneous infection with either S. schenckii or S. brasiliensis conidia. The fungal load was measured at the site of infection, as well as in the liver and spleen. The Th1/Th17/Tregs responses were analyzed in the spleen, while the level of IL-2, IL-4, IL-6, TNF-alpha, IFN-ɣ, IL-17A and IL-10 cytokines were measured at the local site of infection on 24 h postinfections and in sera on the indicated days. S. brasiliensis caused a longer-lasting infection in the skin and chronic systemic dissemination associated to more severe granulomatous lesions. Similar Th1/Th1-Th17/Tregs responses were induced by both S. brasiliensis and S. schenckii on 7th and 21st d.p.i but on 35 d.p.i a reduction of Th1 and Th1-Th17 cells, associated to higher values of Th17/Tregs cells was observed only in S. brasiliensis-infected mice. In summary, S. brasiliensis caused a more severe disease associated with sustained Th17/Tregs responses than S. schenckii in mice.
Keywords: Cytokines; Sporotrichosis; T helper cells; Tregs; Virulence